integral_02

Calculus Level 3

0 e x 3 sin ( x ) x d x = a π b \large \int _{ -\infty }^{ 0 }{ \frac {e^{\frac x{\sqrt 3}}\sin (x)}x} \ dx =\frac { \sqrt { a } \pi }{ b }

If the equation above holds true for positive integers a a and b b . find a + b a+b .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hassan Abdulla
Aug 24, 2017

Let I ( a ) = 0 e a x sin ( x ) x d x I\left( a \right) =\int _{ -\infty }^{ 0 }{ \frac { { e }^{ ax }\cdot \sin { \left( x \right) } }{ x } } dx

d I d a = 0 x e a x sin ( x ) x d x = 0 e a x sin ( x ) d x \frac { dI }{ da } =\int _{ -\infty }^{ 0 }{ \frac { x{ e }^{ ax }\cdot \sin { \left( x \right) } }{ x } } dx=\int _{ -\infty }^{ 0 }{ { e }^{ ax }\cdot \sin { \left( x \right) } dx }

d I d a = e a x ( a sin ( x ) cos ( x ) ) a 2 + 1 0 = 1 a 2 + 1 \frac { dI }{ da } =\frac { { e }^{ ax }\left( a\cdot \sin { \left( x \right) } -\cos { \left( x \right) } \right) }{ { a }^{ 2 }+1 } { | }_{ -\infty }^{ 0 }=\frac { -1 }{ { a }^{ 2 }+1 } //integration by parts

I ( a ) = 1 a 2 + 1 d a = tan 1 ( a ) + C I\left( a \right) =\int { \frac { -1 }{ { a }^{ 2 }+1 } da=-\tan ^{ -1 }{ \left( a \right) } } +C

w h e n a I ( a ) = 0 e a x sin ( x ) x d x = 0 when\quad a\longrightarrow \infty \qquad I\left( a \right) =\int _{ -\infty }^{ 0 }{ \frac { { e }^{ ax }\cdot \sin { \left( x \right) } }{ x } } dx=0 // since x<0 e a x = e = 0 { \Rightarrow e }^{ ax }={ e }^{ -\infty }=0

I ( ) = tan 1 ( ) + C = π 2 + C = 0 C = π 2 I\left( \infty \right) =-\tan ^{ -1 }{ \left( \infty \right) } +C=-\frac { \pi }{ 2 } +C=0\qquad \Rightarrow C=\frac { \pi }{ 2 }

I ( a ) = π 2 tan 1 ( a ) I\left( a \right) =\frac { \pi }{ 2 } -\tan ^{ -1 }{ \left( a \right) }

0 e x 3 sin ( x ) x = I ( 1 3 ) = π 2 tan 1 ( 1 3 ) = π 3 = 1 π 3 \int _{ -\infty }^{ 0 }{ \frac { { e }^{ \frac { x }{ \sqrt { 3 } } }\cdot \sin { \left( x \right) } }{ x } } =I\left( \frac { 1 }{ \sqrt { 3 } } \right) =\frac { \pi }{ 2 } -\tan ^{ -1 }{ \left( \frac { 1 }{ \sqrt { 3 } } \right) } =\frac { \pi }{ 3 } =\frac { \sqrt { 1 } \pi }{ 3 }

a+b=4

Chew-Seong Cheong
Aug 24, 2017

Similar solution with @Hassan Abdulla's

I ( a ) = 0 e a x sin x x d x I ( a ) a = 0 e a x sin x d x By integration of parts = e a x cos x 0 + 0 a e a x cos x d x = 1 + a e a x sin x 0 a 2 0 e a x sin x d x = 1 + 0 a 2 I ( a ) a = 1 a 2 + 1 \begin{aligned} I(a) & = \int_{-\infty}^0 \frac {e^{ax}\sin x}x \ dx \\ \frac {\partial I(a)}{\partial a} & = \int_{-\infty}^0 e^{ax}\sin x \ dx & \small \color{#3D99F6} \text{By integration of parts} \\ & = - e^{ax} \cos x \bigg|_{-\infty}^0 + \int_{-\infty}^0 ae^{ax} \cos x \ dx \\ & = - 1 + ae^{ax} \sin x \bigg|_{-\infty}^0 - a^2 \color{#3D99F6} \int_{-\infty}^0 e^{ax} \sin x \ dx \\ & = - 1 + 0 - a^2 \color{#3D99F6} \frac {\partial I(a)}{\partial a} \\ & = - \frac 1{a^2+1} \end{aligned}

I ( a ) = 1 a 2 + 1 d a = tan 1 a + C where C is the constant of integration. \begin{aligned} \implies I(a) & = - \int \frac 1{a^2+1} \ da \\ & = - \tan^{-1} a + \color{#3D99F6} C & \small \color{#3D99F6} \text{where }C \text{ is the constant of integration.} \end{aligned}

We note that when a = 0 a=0

I ( 0 ) = 0 sin x x d x Replace x with x = 0 sin x x d x = Si ( 0 ) = π 2 where Si ( z ) is the sine integral. C tan 0 = π 2 C = π 2 I ( a ) = π 2 tan 1 a I ( 1 3 ) = π 2 tan 1 1 3 = π 2 π 6 = π 3 = 1 π 3 \begin{aligned} I (0) & = \int_{-\infty}^0 \frac {\sin x}x \ dx & \small \color{#3D99F6} \text{Replace }x \text{ with }-x \\ & = - \int^\infty_0 \frac {\sin x}x \ dx \\ & = {\color{#3D99F6} \text{Si } (0)} = \frac \pi 2 & \small \color{#3D99F6} \text{where } \text{Si } (z) \text{ is the sine integral.} \\ \implies C - \tan{0} & = \frac \pi 2 \\ C & = \frac \pi 2 \\ \implies I(a) & = \frac \pi 2 - \tan^{-1} a \\ I \left(\frac 1{\sqrt 3} \right) & = \frac \pi 2 - \tan^{-1} \frac 1{\sqrt 3} \\ & = \frac \pi 2 - \frac \pi 6 \\ & = \frac \pi 3 = \frac {\sqrt 1 \pi}3 \end{aligned}

a + b = 1 + 3 = 4 \implies a + b = 1 + 3 = \boxed{4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...